Echinococcus granulosus sensu lato and Echinococcus multilocularis: A review. (March 2021) - Woolsey, Ian David; Miller, Andrea L.
Abstract: Echinococcus spp. have a global distribution and are found on every continent except Antarctica. Infections with these parasites are considered extremely serious, contributing to significant morbidity and mortality in addition to substantial economic losses to the livestock industry. Echinococcus granulosus sensu lato (s.l.) and Echinococcus multilocularis, causing cystic echinococcosis (CE) and alveolar echinococcosis (AE) respectively, are the two main species of interest from a human and veterinary perspective. This review collates the current state-of-the-art understanding of these two parasites within four key areas of relevance to human and veterinary professionals: transmission and epidemiology, clinical signs and pathogenesis, diagnosis, and treatment and prevention. This review should serve as a broad introduction to the most important Echinococcus spp. The reader is advised to seek out specific literature on individual diseases and their causative parasites for a deeper understanding. Highlights: Echinococcus spp. have a global distribution, found on every continent except Antarctica Echinococcus granulosus s.l. and E. multilocularis cause cystic echinococcosis and alveolar echinococcosis respectively These diseases are extremely serious, responsible for significant mortality and morbidity and large economic losses Transmission and epidemiology, clinical signs, pathogenesis, diagnosis and treatment and prevention are reviewed